Cooperative spectrum prediction algorithm based on overlapping alliance game. (1st August 2021) - Wang, Xin; Li, Wei; Chen, Yongfeng; Dai, Li
In order to solve the problem of unsatisfactory accuracy of spectrum prediction in a network with multiple primary users, this paper proposes a cooperative spectrum prediction algorithm. The overlapping alliance game is introduced into spectrum prediction. The alliance structure with the highest accuracy of collaborative prediction is selected, and the result with the highest accuracy is obtained. In the experiment, three different collaborative prediction methods are compared and the effects of different parameter values on the simulation results are analysed. The results show that the proposed method has high prediction accuracy, adaptability and robustness.